Implementation of Local Government Performance Accountability System (SAKIP) in Asmat District Government - Raka Pamungkas; Marja Sinurat; Dyah Poespita Ernawati (Lembaga Riset dan Inovasi Al-Matani, 2023)
The purpose of this study is to know and analyze 1) Knowing and understanding the process and causes of the non-optimal implementation of SAKIP in the Asmat Regency Government, 2) Knowing and understanding what factors affect the optimal implementation of SAKIP in the Asmat Regency Government. 3) Knowing and understanding the implementation of SAKIP in the Asmat Regency Government. The research method uses a qualitative approach, data collection techniques are observation, interviews, and documentation. The results of this research are: 1) The implementation of SAKIP in the Asmat Regency Government is good, which shows that the level of effectiveness and efficiency of budget use is quite good when compared to its performance achievements, 2) Supporting factors: the development of a culture of bureaucratic performance and the implementation of results-oriented governance in the Asmat Regency Government has begun to run well, 3) the leaders are directly involved in providing direction to the lower ranks in the process of planning and evaluating performance and budget, both annual and medium-term.